Internalized HIV Stigma and Mindfulness: Associations With PTSD Symptom Severity in Trauma-Exposed Adults With HIV/AIDS. (January 2016) - Gonzalez, Adam; Locicero, Briana; Mahaffey, Brittain; Fleming, Crystal; Harris, Jalana; Vujanovic, Anka A.
Rates of both traumatic event exposure and posttraumatic stress disorder (PTSD; 22%-54%) are disproportionately elevated among people living with HIV/AIDS (PLHA). Trauma and related psychopathology significantly affect quality of life and disease management in this patient population. The current study examined associations between internalized HIV stigma, mindfulness skills, and the severity of PTSD symptoms in trauma-exposed PLHA. Participants included 137 PLHA (14.6% female; M age = 48.94, SD = 8.89) who reported experiencing on average, five ( SD = 2.67) traumatic events; 34% met diagnostic criteria for PTSD. Results indicate that after controlling for sex, age, education, and number of traumatic events, internalized HIV stigma was positively related to overall PTSD symptom severity (β = .16, p < .05) and severity of re-experiencing (β = .19, p < .05) and hyper-arousal (β = .16, p = .05), but not avoidance, PTSD symptom clusters. Among the mindfulness facets measured, acting with awareness was uniquely negatively related to the overall severity of PTSD symptoms (β = − .25, p < .01) and the severity of re-experiencing (β = − .25, p < .05), avoidance (β = − .25, p < .05), and hyper-arousal (β = − .29, p < .01) PTSD symptom clusters. These effects were observed after accounting for covariates and shared variance with other mindfulness facets. Theoretically, the present findings suggest that internalized HIV stigma may serve as a vulnerability factor for the severity of certain PTSD symptoms, whereas acting with awareness may function as a protective or resiliency factor for the severity of PTSD symptoms. Implications for the treatment of trauma-exposed PLHA are discussed.